(untitled) (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
Jerusalem artichoke was brought to Europe in 1627, first to France, and from there to Italy, Holland and other countries. In Russia, Jerusalem artichoke appeared in the XVIII century, and people used it as a medicinal plant, and the infusion of tubers on wine was used to treat cardiovascular respiratory diseases.